DETEKSI DINI TERKAIT FLAT FOOT DI KB-TK AL-QURAN TERPADU BINTANGKU SURAKARTA - Arif Pristianto; Hafizhah Putri Ilma Ilma Darojati; Zahwa Putri Nurhandrita; Arzhuma Arza Lazuardy; Annisa Dwi Rahayu (Jurnal Pengabdian Masyarakat Multidisiplin, 2022)
Early age is the age when the pattern of growth and development is very rapid. This must be accompanied by proper education regarding growth and development, otherwise at this age the child will be susceptible to abnormalities. These disorders can be in the form of gait disorders. One of the most important parts that affect the biomechanical and musculoskeletal structures of the foot is the arch of the foot or arcus pedis. The consequences of an arch that does not grow normally include balance disorders, fatigue when walking for a long time, continuing deformity, and pain. Flat foot is the most common deformity or deformity of the foot in children. The activity was carried out at the TK-KB Al-Quran Terpadu Bintangku Surakarta school with a total of 60 children. The purpose of this activity is to see the prevalence of flat foot and preventive measures are delivered in the form of early detection using the Clarke's angle test. This program was carried out in May 2022. The results of this activity had a good impact in helping to increase children's knowledge about flat foot and it was found that the prevalence of cases was mostly experienced by males than females. The author hopes that schools can continue to routinely check flat foot activities considering that flat feet often do not cause symptoms, so early age screening is needed.